2021
DOI: 10.1177/00178969211051054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the South Asian Adolescent Diabetes Awareness Program (SAADAP) on diabetes knowledge, risk perception and health behaviour

Abstract: Objective: Evidence suggests the increased prevalence of diabetes among South Asian (SA) adolescents is due to their genetic risk profile. The South Asian Adolescent Diabetes Awareness Program (SAADAP) is a pilot intervention for SA youth in Canada with a family history of type 2 diabetes mellitus (T2DM). We sought to investigate changes in (1) diabetes knowledge and associated risk factors, (2) risk perception and (3) health behaviours among adolescents participating in SAADAP. Design: One-group pre-test, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Here, the unique cultural contexts of different ethnic groups—some of which place distinctive emphasis on responsibilities towards families and/or communities—may present different opportunities and challenges [ 35 , 36 , 64 67 ]. For example, a study conducted in the Netherlands found that, compared to Dutch patients, Surinamese South Asian patients tended to report higher levels of concern over their relatives’ T2D risk [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the unique cultural contexts of different ethnic groups—some of which place distinctive emphasis on responsibilities towards families and/or communities—may present different opportunities and challenges [ 35 , 36 , 64 67 ]. For example, a study conducted in the Netherlands found that, compared to Dutch patients, Surinamese South Asian patients tended to report higher levels of concern over their relatives’ T2D risk [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the peer educational intervention had positive effects on adolescents’ knowledge. Banerjeea et al also witnessed significant differences regarding the knowledge of the definition, symptoms, and complications of type-2 diabetes after intervention among adolescents in the treatment group [ 21 ]. In a study aiming at investigating the relationship between preventive intervention and behavior-determining factors, Braver concluded that education could heighten knowledge among people prone to type-2 diabetes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the unique cultural contexts of minoritised ethnic groups-some of which place distinctive emphasis on responsibilities towards families and/or communities-may present different opportunities and challenges (35,36,(63)(64)(65)(66). One study conducted in the Netherlands found that, compared to Dutch patients, Surinamese South Asian patients tended to report higher levels of concern over their families' and relatives' T2D risk (65).…”
Section: Using Familial Variables To Leverage Genetic Risk Informationmentioning
confidence: 99%